2020
DOI: 10.3126/nmj.v3i1.28221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hearing loss by Pure Tone Audiometry in Type 2 Diabetes Mellitus

Abstract: Introduction: The association of hearing loss and diabetes has been under research for many years. The hearing loss in diabetes in our population has not been studied extensively. The objective of this study was to compare the hearing threshold between type 2 diabetic patients and age- and sexmatched controls. Materials and Methods: A comparative study was done in the Department of ENT, Kathmandu Medical College from October 2019 to February 2020. The hearing threshold, of 40 type 2 diabetics patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“… 47 The results of the current study suggested that individuals with a long duration of T2DM had a higher chance of developing SNHI than those with a short-term duration. This was in line with studies done in Mexico, 35 Indonesia, 48 Turkey, 49 Nepal, 1 Iran, 29 China, 37 Jammu, 46 India, 50 Saudi Arabia, 25 and South Africa. 26 The possible reason might be that chronic hyperglycemia affects the inner ear nerve tracts and blood vessels by increased reactive oxygen species.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“… 47 The results of the current study suggested that individuals with a long duration of T2DM had a higher chance of developing SNHI than those with a short-term duration. This was in line with studies done in Mexico, 35 Indonesia, 48 Turkey, 49 Nepal, 1 Iran, 29 China, 37 Jammu, 46 India, 50 Saudi Arabia, 25 and South Africa. 26 The possible reason might be that chronic hyperglycemia affects the inner ear nerve tracts and blood vessels by increased reactive oxygen species.…”
Section: Discussionsupporting
confidence: 90%
“… 27 The consistency in study design and participant characteristics may account for the observed trend. However, the findings from this study revealed lower values compared to similar research conducted in Japan (60.2%), 28 Iran (85%), 29 Nepal (72.5%), 1 India (58%), 30 North India (81%), 31 and Nigeria (71.8%). 32 This possible discrepancy might be due to natural disasters such as volcanic eruptions, flooding, and tsunamis that regularly affect Asian countries.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This finding was less compared to earlier studies where the prevalence of hearing loss in diabetes mellitus patients quoted from a range of 33.7% to 97.6%. [15][16][17][18][19] We did not find clarification for such a broad variation, but it could be attributed to the study methodology of differences in inclusion criteria, demographics, type and duration of diabetes mellitus, the clinical and biochemical status of diabetes mellitus patients. The current study did not limit the recruitment of study participants according to the duration of disease, age, or gender.…”
Section: Discussionmentioning
confidence: 99%